3D printing of food: pretreatment and post-treatment of materials. Issue 14 (5th August 2020) - He, Chang; Zhang, Min; Fang, Zhongxiang
Abstract: Background: Food 3 D printing is an emerging food processing technology. Due to the advantages of functionalization, customization, personalized nutrition design, simplified supply chain and broadening existing food materials, 3 D printing has been extensively studied in the food sector in the past decade. Many factors influence the accuracy and quality of food 3 D printing, which are also the challenges to researchers. Currently, most of the research focuses on the development of printable materials and control of printing parameters to improve the printing accuracy and product quality. However, the influence of material pretreatment methods and post-processing techniques on food 3 D printing have received less attention. Main content: By collecting the available data and research, this paper analyzes the effect of pretreatment technologies (crushing, gelation, etc.) and post-treatment technologies (cooking, drying, fast cooling technology, 4 D printing, etc.) on the accuracy and shape fidelity of 3 D printed food products. It also summarizes the current challenges of food 3 D printing and proposes some thoughts on the future development of this technology.